2017
DOI: 10.1002/1878-0261.12016
|View full text |Cite
|
Sign up to set email alerts
|

FAM83 family oncogenes are broadly involved in human cancers: an integrative multi‐omics approach

Abstract: The development of novel targeted therapies for cancer treatment requires identification of reliable targets. FAM83 (‘family with sequence similarity 83’) family members A, B, and D were shown recently to have oncogenic potential. However, the overall oncogenic abilities of FAM83 family genes remain largely unknown. Here, we used a systematic and integrative genomics approach to investigate oncogenic properties of the entire FAM83 family members. We assessed transcriptional expression patterns of eight FAM83 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
102
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 32 publications
(57 reference statements)
6
102
0
1
Order By: Relevance
“…The FAM83 proteins were recently identified as novel transforming oncogenes that function as intermediaries in EGFR/RAS signaling, and the oncogenic properties were dependent upon the conserved DUF1669 domain (Cipriano et al, , ). It was also demonstrated that these proteins, including FAM83H, were overexpressed in many human tumors (Cipriano et al, ; Snijders et al, ). Therefore, FAM83H might play a role in cell proliferation or survival mediated by EGFR/RAS signaling, presumably through its DUF1669 domain, which is essential for certain critical physiological functions.…”
Section: Discussionmentioning
confidence: 98%
“…The FAM83 proteins were recently identified as novel transforming oncogenes that function as intermediaries in EGFR/RAS signaling, and the oncogenic properties were dependent upon the conserved DUF1669 domain (Cipriano et al, , ). It was also demonstrated that these proteins, including FAM83H, were overexpressed in many human tumors (Cipriano et al, ; Snijders et al, ). Therefore, FAM83H might play a role in cell proliferation or survival mediated by EGFR/RAS signaling, presumably through its DUF1669 domain, which is essential for certain critical physiological functions.…”
Section: Discussionmentioning
confidence: 98%
“…FAM83A is involved in regulating a variety of different tumor-related signaling pathways, including the EGFR, RAS/RAF/MEK/ERK, and PI3K/AKT/mTOR pathways (3,4). The overexpression of FAM83A has been shown in lung, breast, testicular, and bladder cancers and is associated with promoting the development of cancers (7)(8)(9)(19)(20)(21)(22). Li et al (3) reported that FAM83A is highly expressed in lung cancer tissues, especially LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Il6st is in the royalblue module, along with transcripts that are significantly enriched for the GO term, "positive regulation of cytokine production". The FAM83 family consists of eight members, several of which are increased in expression or copy number in various cancers, and are downstream of the phosphatidylinositol 3-kinase and epidermal growth factor receptor pathways (SNIJDERS et al 2017). …”
Section: Discussionmentioning
confidence: 99%